Strategi Komunikasi Persuasif Penyiar Siaran Langsung Facebook Untuk Sikap Audiens Dalam Pemberian Gift - Rasyid, La Ode Muhamad; Hastuti , Hastuti; Putra , M. Rizal Ardiansyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
The increasing use of Facebook Pro live streaming features by the community in Jayabakti Village as a means of social interaction and economic opportunity reflects a shift in digital communication behavior. In this context, broadcasters are required to employ effective persuasi communication strategies to encourage audience engagement, particularly in the form of sending virtual gifts. This study aims to explore the persuasive communication strategies employed by broadcasters on Facebook Pro live streaming to influence audience behavior in giving gift. This research uses a descriptive qualitative method with data collected through in-depth interviews and observations involving five active Facebook Pro broadcasters. The data were analyzed using Social Influence Theory, focusing on five principles: liking, social proof, authority, reciprocity, and commitment and consistency. The results show that the success of broadcasters in encouraging audience gift-giving is significantly influenced by the implementation of these persuasive strategies. Broadcasters build emotional closeness (liking), display social proof through viewer and gift counts (social proof), foster trust through consistency and transparency (authority), reciprocate audience attention (reciprocity), and maintain engagement through routine and repeated appeals (commitment and consistency). These strategies are applied synergistically to create interactive, familiar relationships that influence audience decisions to offer support. This study contributes to the field of digital communication by demonstrating that persuasive communication in live streaming not only conveys information but also builds social relationships that can drive real audience actions.